Gabe’s Stories: Intersecting Spirituality with Speech-Related (Dis)ability - Norton, Nadjwa (Disability Studies Quarterly, 2009)
This one-year multicultural feminist critical narrative inquiry focuses on how one Puerto Rican/Black working class male draws on his spirituality to negotiate his speech-related (dis)ability. By utilizing multiple qualitative methods, the researcher and child-co-researcher illuminate how he draws on his agencies and intersecting identities to negotiate teaching people lessons, teasing, and language differences. This paper highlights the abilities of children to name their spiritualities and to tell stories that clearly illustrate the intersections of spiritualities and (dis)abilities. It serves to expand constructions of children as knowledge producers, agents, teachers, justice seekers, and shapers of learning environments. Understanding children’s negotiations of interpersonal school structures has the potential to create more equitable structures that affirm the identities, increase academic success, and support the agencies of children who are marginalized across the intersecting identities. Key Words: Speech-Related Disabilities, Urban, Spirituality, Education, Narrative Inquiry